Design of a Lightning Protection System for an Overhead 3 kV DC Electrified Railway Line: A Case Study from South Africa - Kelishia Radhalal; Chandima Gomes (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
A protection scheme is proposed for the 3 kV DC railway, in Kwa-Zulu Natal province, a region with a high lightning occurrence density. The surge protection was sought by implementing three metal-oxide surge arresters and an overhead ground wire. The purpose of these arresters is determined by their location in the circuit and the points that are vulnerable to adverse lightning effects: an arrester is installed to protect insulators between overhead lines and the supporting metallic mast, an arrester is installed to protect the point of contact between a stationary power supply wire and the train, and an arrester is installed to protect apparatus associated with the running tracks (return rail). An isolated earthing system is explored, and the effects of surge impedances and footing resistances are discussed. The voltage dropped across relevant vulnerable components and energy absorbed by the system components are determined by the simulation software Simulink. These results are compared with a railway system outfitted with the designed lightning protection mechanisms. Lightning currents are injected into the system using Heidler function where the parameters are in compliance with lightning protection standards. It is observed that the protection mechanisms defend susceptible components to a specified level. This demonstrates the success of the design in accordance with arrester protection levels (73.3 kV) and equipment withstand capabilities (a basic insulation level of 143 kV). This offers a protection margin of 95%. The largest percentage overshoot in the system is 39%, and this value is substantiated using reflection phenomena.